Passive and Active Removal of Marine Microplastics by a Mushroom Coral (Danafungia scruposa) - Corona, Elena; Martin, Cecilia; Marasco, Ramona; Duarte, Carlos M. (Frontiers in Marine Science, 2020)
Although millions of tons of plastics end up in oceans each year, floating plastics account for only about 1% of all plastic inputs in the ocean. Particularly, microplastics below 1 mm in length, are missing in surface waters due to removal processes like ingestion by marine animals, biofouling and sinking. Here, we studied how a species of mushroom corals (Danafungia scruposa), common in the Maldives, contributed to the removal of microplastics from the water suspension through active (ingestion) and passive (adhesion to the surface) mechanisms. We evaluated if removal rates were affected by the presence of the coral natural prey (i.e. Artemia salina) and by biofouling on the surface of the microplastic. We found that the coral quickly interacts both actively and passively with microplastics and that the probability for the coral to ingest and retain microplastics was higher when the surface of the microplastic was biofouled. We also found that passive adhesion of microplastics was the primary mechanism through which corals sequester microplastics from the water column.